A Prospective Randomized Study Evaluating the Effect of Perioperative NSAIDs on Opioid Consumption and Pain Management After Ankle Fracture Surgery. Issue 3 (14th September 2018) - McDonald, Elizabeth; Daniel, Joseph; Nicholson, Kristen; Shakked, Rachel; Raikin, Steven; Pedowitz, David; Winters, Brian
Category: Trauma Introduction/Purpose: Currently there is an epidemic in the United States regarding opioid abuse. This has resulted in strict government prescribing regulations throughout the country and increasing efforts by orthopaedic surgeons to better manage postoperative narcotic analgesia. Non-steroidal anti-inflammatory drugs (NSAIDs) can serve as a powerful adjunct in managing postoperative pain and in turn minimize the need for opioid medications. It has recently been shown that ketorolac can be used after open reduction and internal fixation (ORIF) of ankle fractures without interfering with bone healing. Therefore, we set out to evaluate whether including ketorolac in the postoperative drug regimen reduces opioid consumption and pain after ORIF of ankle fractures. Methods: 128 patients undergoing ORIF of an ankle fracture were prospectively randomized to treatment with or without ketorolac. Patients also had the option to simultaneously undergo regional anesthesia. Patients assigned to the treatment group were given 30 mg of IV ketorolac intraoperatively; prescribed 20 tablets of ketorolac 10 mg PO Q6 H and 30 tablets of Oxycodone/Acetaminophen 5/325 Q4-6 H PRN. Patients assigned to the control group were given 30 tablets of oxycodone/acetaminophen 5/325 Q4-6 H PRN only. A survey was distributed via Research Electronic Data Capture (REDCap) on postoperative days 1-7. Patients were asked to report their daily opioid consumption, pain level using the Visual Analog Scale (VAS), satisfaction with pain management, and side effects. Intention-to-treat analysis was performed. Normality of data was tested using the Shapiro-Wilk test. Differences between the control and treatment groups were tested using Mann-Whitney U or Student's t-tests. Results: 105/128 (82%) patients with mean BMI of 29.3 completed all study requirements. 54 received ketorolac with opioid medication and 51 received opioids alone. 43 men (41%) and 62 women (59%) participated with mean age of 48 years. Patients receiving ketorolac required less oxycodone/acetaminophen (p<0.013) and reported less pain (p<0.048) during postoperative days 1 and 2 compared to control patients(Figure 1). While opioid consumption did not significantly differ after day 2, patients treated with ketorolac maintained less pain (days 1-4, p<0.028); better sleep (days 1-5, p<0.037); lower frequency of pain (days 1-3; p<0.017); and greater satisfaction with pain management (days 1-3, p<0.047). Hypersensitivity was significantly less on day 1 (p=0.036) and paresthesias on day 3 (p=0.011). Surprisingly, there was no difference in nausea/constipation between groups (p>0.139). Conclusion: The addition of ketorolac to the postoperative drug regimen significantly reduced pain, while decreasing the use of opioid medication following ORIF of ankle fractures early in the postoperative period. Better pain management during postoperative days 1 and 2 is particularly important because patients on average consume the most opioids during this time. With the assurance that ketorolac does not interfere with bone healing, this NSAID is a valuable tool for helping patients manage postoperative pain with less narcotic analgesia.